Asthma - Andrew O’Keefe; Lori Connors; Ling Ling; Harold Kim (Allergy, Asthma & Clinical Immunology)
Abstract Asthma is one of the most common respiratory disorders in Canada, however, many Canadians with asthma remain poorly controlled. In most patients, control can be achieved through appropriate therapy, including: inhaled corticosteroids (ICS), combination ICS/long-acting beta2-agonists (LABA), “triple therapy” with ICS/LABA/long-acting muscarinic receptor antagonist (LAMA), and biologic therapies. The medical management of severe asthma, in particular, has changed dramatically with the incorporation of biologics in asthma treatment plans. Allergen-specific immunotherapy represents a potentially disease-modifying therapy for many patients with asthma; it must only be prescribed by physicians with appropriate training in allergy. Other essential components of asthma management include: regular monitoring of asthma control and risk of exacerbations; patient education and written asthma action plans; assessing barriers to treatment and adherence to therapy; adequate management of comorbidities (e.g., allergic rhinitis) and reviewing inhaler device technique. This article provides a review of current literature and guidelines for the appropriate diagnosis and management of asthma in adults and children.